Entanglement of UPRER in Aging Driven Neurodegenerative Diseases - Rahman, Safikur; Jan, Arif Tasleem; Ayyagari, Archana; Kim, Jiwoo; Kim, Jihoe; Minakshi, Rinki (Frontiers in Aging Neuroscience, 2017)
The endoplasmic reticulum (ER) is an indispensable cellular organelle that remains highly active in neuronal cells. The ER bears the load of maintaining protein homeostasis in the cellular network by managing the folding of incoming nascent peptides; however, the stress imposed by physiological/environmental factors can cause ER dysfunctions that lead to the activation of ER unfolded protein response (UPRER). Aging leads to deterioration of several cellular pathways and therefore weakening of the UPRER. The decline in functioning of the UPRER during aging results in accumulation of misfolded proteins that becomes intracellular inclusions in neuronal cells, resulting in toxicity manifested as neurodegenerative diseases. With ascension in cases of neurodegenerative diseases, understanding the enigma behind aging driven UPRER dysfunction may lead to possible treatments.